Modelling Traffic on Road Junctions on Parallel Computing Systems Using Cellular Automata Approach - Chechina, Antonina Aleksandrovna; Churbanova, Natalia Gennadievna; Trapeznikova, Marina Aleksandrovna (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The paper deals with traffic flow modelling and simulation on supercomputer systems. The created mathematical model is based on cellular automata (CA) approach and allows to depict multilane traffic on various complex road configurations. The numerical algorithms for the model are designed for supercomputer calculations. The main focus of this research is the validation of the created models and the comparison with results obtained by other researchers, as well as with experimental data. Several test problems were solved to carry out the comparison. The results obtained show that the model represents traffic flow characteristics efficiently and correctly and can be used for real-life traffic predictions.